NEW TAXA IN MALESIAN CUCURBITACEAE - RUGAYAH RUGAYAH (BRIN Publishing (Penerbit BRIN), 1998)
In the wide-spread cucurbitaceous SE Asian genus Trichosanthes 5 new Malesian taxa are described by Rugayah, viz Trichosanthes auriculata Rugayah, T. beccariana Cogn. subsp. pusilla Rugayah, T.montana Rugayah, T. pendula Rugayah, and T. rotundifolia Rugayah. The new monotypic genus Borneosicyos, with the sole species B.simplex de Wilde, endemic of Sabah, is described by de Wilde.